Spatial Implications of Minimum Wages - Thiess Büttner; Alexander Ebertz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
This paper addresses possible consequences of a minimum wage in a spatial context. An empirical analysis utilizing German data shows that a signifcant spatial wage structure exists and that, as a consequence, the share of workers earning wages below a minimum wage will be particularly high in rural counties even if we control for educational and occupational differences. A theoretical analysis discusses the implications for the spatial structure of the economy and shows that while the wages in the countryside will be affected positively, wages will decline in the city, where employment and population rise. Workers in the city will further suffer from an increase in housing costs. This supports concerns that urban poverty might increase as a result of the introduction of a minimum wage.
Keywords: J30; J60; R12; 330; Minimum Wages; Urban Poverty; Spatial Wage Structure; Mobility; Economies of Agglomeration